Gender Discourses as a ‘Technology of Power’ in Nepalese Primary Level Textbooks - Paneru, Pragya (Molung Educational Frontier, 2019)
The Gender gap is one of the most prominent problems in the context of Nepal. Even if Nepal constitution promotes gender equality and equity, there is still a huge gap between male and female. Women lag in literary percentage, nutritional health conditions, ownership, and employment opportunities. One of the obstacles in the path of gender equality is our systemic education materials especially our textbooks which reinforce the stereotypical concept of male and female through textbook representations. Researchers have shown that gender stereotypes have been seen in the textbooks of highly developed countries like America, Australia, and Hongkong. In this context, all the compulsory textbooks of grade four and five prescribed by the Curriculum Development Centre in the context of Nepal were observed. In all the books, stereotypical representations of male and female characters were found. Most of the men and women were presented doing conventional gender roles, and male-centered themes are found in the narratives. This research claims that when conventional attitude regarding gender is transferred to young children, it ultimately reproduces similar gendered personalities and helps to maintain the gender gap. This research uses the concept of ‘technology of power’ by Foucault to interpret gender representations in textbooks. A Ccritical Discourse Analysis has been used to analyze the data from textbooks. The findings suggest that there are biased gender representations suggesting stereotypes and gender binary which could potentially affect the learners both male and female as it fosters false knowledge regarding gender and overburdens the male whereas humiliates the females.